Resistance Against Dutch Colonialism in Kluet 1925-1927 - Anzalimuddin, Anzalimuddin; Umar, Mawardi; Kesuma, T Bahagia (Universitas Negeri Padang, 2024)
After the capture of Sultan Aceh Muhammad Daud Syah in 1903, resistance against the Dutch had begun to subside, so several views emerged that the Aceh war against the Dutch had ended. The study's objectives are the background and reasons for the emergence of new resistance in 1925 and the resistance strategy against the Dutch Colonial in Kluet in 1925-1927. To achieve these objectives, this study uses a historical method. It is known that the resistance in Kluet was caused by various factors, namely, Dutch arbitrariness in development projects, revenge, Dutch interference in the Kluet customary government, and religious factors. The fighters' strategy in carrying out resistance was a guerrilla warfare strategy. The emergence of resistance against the Dutch in the Kluet region only occurred in 1925-1927 when other areas were calm, which was motivated by two things, namely Dutch intervention in the Kluet regional government with the signing of the Pledge Letter in 1925 which caused chaos among the keujreun, uleebalang, uleebalang Potong, village heads and civilians. In addition, it was also motivated by mental problems, namely, the views of the fighters, who previously considered resistance against the Dutch impossible, suddenly changed after seeing the T.R. Angkasah group protesting against the Dutch. This action ignited the spirit of the fighter groups to dare to resist consistently